Recommendations for Manufacturers of Mine Suspended Monorail Transportation Means in the Context of Entry the Technical Data Into the Aiding Configuration System - Tokarczyk Jarosław; Dudek Marek (Management Systems in Production Engineering)
The article presents recommendations that should be followed by the manufacturers of underground mine suspended monorail transportation means (auxiliary mine transport equipment), used on inclinations up to 45 degrees, in the context of using the technical data contained in the instructions for their entry into the Safe Trans Design (STD) database. Safe Trans Design system was developed by KOMAG Institute of Mining Technology in 2013. At the same year it was implemented in the mines of Jastrzębska Coal Company (JSW S.A.). Its purpose is to help (assist) designers of suspended monorail transportation system to carry out traction calculations. These calculations are required in the process of preparing documentation for the transportation system. Technical data included in the database, should contain information for: suspended monorail locomotives, brake trolleys, modular carrying sets (high-load beams), sets of hoists, cabins, and benches for movement of people, containers, and special wagons. Examples of generalized input data for the selected components of the suspended transportation unit (passenger cabin and suspended locomotive), in the context of their use in traction calculations, are presented. An example of importing the graphical load-carrying characteristic for suspended monorail locomotive, using digitalization and the CAD system (AutoCAD), is also presented.